Quel Moyen Âge dans l’édition pour la jeunesse ? - Myriam White-Le Goff (Itinéraires)
This paper deals with the reference to the Middle Ages or to medieval literature in books dedicated to children or young readers. I will expose the different types of books and their main characteristics and will focus on the medieval literature published for children. It appears that the Middle Ages are often associated with local identity and folklore or to school and education. The writers use the very malleability of medieval literature and often consider reference to the Middle Ages as a special opportunity to go back to a beloved childhood, providing a peculiar vision of the world.